Hereditary cancer registries improve the care of patients with a genetic predisposition to cancer: contributions from the Dutch Lynch syndrome registry - Hans F. A. Vasen; Mary E. Velthuizen; Jan H. Kleibeuker; Fred H. Menko; Fokke M. Nagengast; Annemieke Cats; Andrea E. van der Meulen-de Jong; Martijn H. Breuning; Anne J. Roukema; Inge van Leeuwen-Cornelisse; Wouter H. de Vos tot Nederveen Cappel; Juul T. Wijnen (Familial Cancer, 2016)

Meta‐barcoding of ‘dirt’ DNA from soil reflects vertebrate biodiversity - KENNETH ANDERSEN; KAREN LISE BIRD; MORTEN RASMUSSEN; JAMES HAILE; HENRIK BREUNING‐MADSEN; KURT H. KJÆR; LUDOVIC ORLANDO; M. THOMAS P. GILBERT; ESKE WILLERSLEV (Molecular Ecology, 2012)
DNA molecules originating from animals and plants can be retrieved directly from sediments and have been used for reconstructing both contemporary and past ecosystems. However, the extent to which such ‘dirt’ DNA reflects taxonomic richness and structural diversity remains contentious. Here, we couple second generation high‐throughput sequencing with 16S mitochondrial DNA (mtDNA) meta‐barcoding, to explore the accuracy and sensitivity of ‘dirt’ DNA as an indicator of vertebrate diversity, from soil sampled at safari parks, zoological gardens and farms with known species compositions. PCR amplification was successful in the full pH range of the investigated soils (6.2 ± 0.2 to 8.3 ± 0.2), but inhibition was detected in extracts from soil of high organic content. DNA movement (leaching) through strata was evident in some sporadic cases and is influenced by soil texture and structure. We find that DNA from the soil surface reflects overall taxonomic richness and relative biomass of individual species. However, one species that was recently introduced was not detected. Furthermore, animal behaviour was shown to influence DNA deposition rates. The approach potentially provides a quick methodological alternative to classical ecological surveys of biodiversity, and most reliable results are obtained with spatial sample replicates, while relative amounts of soil processed per site is of less importance.

Analysis of missense variants in the PKHD1-gene in patients with autosomal recessive polycystic kidney disease (ARPKD) - Monique Losekoot; Cathleen Haarloo; Claudia Ruivenkamp; Stefan J. White; Martijn H. Breuning; Dorien J. M. Peters (Human Genetics, 2005)

Bannayan–Riley–Ruvalcaba syndrome: further delineation of the phenotype and management of PTEN mutation-positive cases - Y.M.C. Hendriks; J.T.C.M. Verhallen; J.J. van der Smagt; S.G. Kant; Y. Hilhorst; L. Hoefsloot; K.B.-M. Hansson; P.J.C. van der Straaten; H. Boutkan; M.H. Breuning; H.F.A. Vasen; A.H.J.T. Bröcker-Vriends (Familial Cancer, 2003)